Pediatric interventional radiology : handbook of vascular and non-vascular interventions - Marshalleck, Francis E.; Temple, Michael (Springer New York, 2014)
About 25 years ago, a few pioneering radiologists began performing "special procedures" in pediatric patients.  Since that time, the practice of pediatric interventional radiology (PIR) has come a long way.  Pediatric Interventional Radiology highlights the unique elements of pediatric practice that are necessary to provide safe patient care. It discusses all major vascular and non-vascular PIR procedures, and is organized to be procedure-specific with secondary-area classification. Each chapter contains introductory descriptions of disease processes, indications for intervention, technical information about the procedures and post-procedure care. Summaries at the end of each chapter provide a quick guide to the major topics covered. The book also includes numerous images and illustrations that make it easy to access to "What You Need to Know" information, such as a list of the size/age appropriate equipment that is commonly used to perform procedures. This book serves as a valuable resource for residents, fellows, adult interventionalists, radiologists, and anyone who performs or wishes to obtain further knowledge on minimally invasive, image-guided procedures in infants and children.